A Study on MTHFR C677T Gene Polymorphism and Alcohol Dependence among Meiteis of Manipur, India. (1st October 2014) - Singh, Huidrom Suraj; Salam, Kabita; Saraswathy, Kallur Nava
Abstract : Chronic alcohol consumption is reported to be associated with increase in plasma homocysteine levels which is further influenced by the polymorphism in methylenetetrahydrofolate reductase ( MTHFR ) gene. The present study aims to understand the extent of the MTHFR C677T polymorphism in alcohol dependent (AD) cases of Meiteis of Manipur, a Mendelian population of India. MTHFR C677T polymorphism was screened in 313 controls and 139 alcohol dependent (AD) cases who all met DSM-IV criteria for alcohol dependence. Both AD cases and controls were unrelated up to 1st cousin. Among the control group, different drinking patterns like abstainer/nondrinkers (NDs), occasional drinkers (ODs), and moderate drinkers (MDs) are included. Both the groups were found to be in Hardy-Weinberg equilibrium (P > 0.05 ). Genotypic and allelic frequency distribution of MTHFR C677T polymorphism did not differ significantly between AD cases and controls (P > 0.05 ). However, individuals carrying mutant (T) allele show more than 1-fold increased risk for AD though not significant (OR = 1.43; 95% CI 0.41–5.01, P > 0.05 ). In conclusion, MTHFR C677T polymorphism is not found to be risk marker for AD in present studied population. However, higher prevalence of the mutant T allele may exacerbate deleterious health risk in future especially among alcohol drinkers.